A 2D system approach to the design of a robust modified repetitive-control system with a dynamic output-feedback controller - Zhou, Lan; She, Jinhua; Zhou, Shaowu (Zielona Góra: Uniwersytet Zielonogórski)
This paper is concerned with the problem of designing a robust modified repetitive-control system with a dynamic output feedback controller for a class of strictly proper plants. Employing the continuous lifting technique, a continuous-discrete two-dimensional (2D) model is built that accurately describes the features of repetitive control.
Keywords: repetitive control; dynamic output-feedback; two-dimensional system; singular-value decomposition; linear matrix inequality